PROSPECTS FOR USING PLANT ADDITIVES IN THE PRODUCTION OF MEAT AND FISH PRODUCTS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The growing interest in plant-based additives has opened new horizons for the food industry, particularly in the production of meat and fish products. This paper explores the prospects of incorporating plant-based additives into these products, emphasizing their functional, nutritional, and sustainability benefits. Plant additives, such as proteins, fibers, and natural preservatives, have been proven to enhance product quality, improve shelf life, and align with the increasing demand for health-conscious and environmentally friendly foods. The study analyzes the current trends, technological challenges, and the potential impact of these innovations on the food industry in Uzbekistan. Recommendations for future applications and research are also provided.